Input Indicators of Audit Quality: A Framework Based on Literature Review - Mutiara Syalwa; Yulia Saftiana; Hendra Susanto; Hasni Yusrianti (Jurnal Kewirausahaan dan Bisnis, 2024)
Audit quality is a fundamental aspect of ensuring the transparency and accountability of financial statements. This study investigates the input factors influencing audit quality, based on the IAASB (2014) framework, focusing on auditor values, ethics, attitudes, knowledge, skills, and experience. Using a systematic literature review (SLR) approach, 34 articles published between 2014 and 2024 were analyzed to identify key factors and theoretical perspectives, including Agency Theory and Stakeholder Theory. The findings highlight the significant impact of input factors such as auditor competence, independence, and ethical conduct on audit quality, while also revealing inconsistencies due to differences in research contexts, methodologies, and external influences like regulatory changes. By addressing these gaps, this study offers new insights into the relationship between input factors and audit reliability, emphasizing the need for integrated frameworks to enhance audit practices and ensure financial accountability.Keywords: audit quality, auditor competence, ethical conduct, systematic literature review (SLR)